2017
DOI: 10.1038/s41598-017-15812-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicted molecular targets and pathways for germacrone, curdione, and furanodiene in the treatment of breast cancer using a bioinformatics approach

Abstract: Germacrone, curdione, and furanodiene have been shown to be useful in the treatment of breast cancer but the pharmacological mechanism of action is unclear. In this paper, we explored a new method to study the molecular network and function of Traditional Chinese Medicine (TCM) herbs and their corresponding ingredients with bioinformatics tools, including PubChem Compound Database, BATMAN-TCM, SystemsDock, Coremine Medical, Gene ontology, and KEGG. Eleven targeted genes/proteins, 4 key pathways, and 10 biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…At present, many databases made a significant contribution to the development of systems biology, such as the Bioinformatics Analysis Tool for Molecular mechanism of TCM (BATMAN-TCM) developed by Liu (Liu et al, 2016). BATMAN-TCM was applied in the study exploring the mechanism of Curcuma longa L (E'Zhu) in the treatment of breast cancer (Kong et al, 2017). In this article, we try to explore the pharmacological mechanism of KX in treating RA and explain how the drugs combination of herbs works on reducing adverse reactions.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many databases made a significant contribution to the development of systems biology, such as the Bioinformatics Analysis Tool for Molecular mechanism of TCM (BATMAN-TCM) developed by Liu (Liu et al, 2016). BATMAN-TCM was applied in the study exploring the mechanism of Curcuma longa L (E'Zhu) in the treatment of breast cancer (Kong et al, 2017). In this article, we try to explore the pharmacological mechanism of KX in treating RA and explain how the drugs combination of herbs works on reducing adverse reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al reported that in the antiviral test in vitro, germacrone showed high antiporcine reproductive respiratory syndrome virus (PRRSV) infection activity by inhibiting the replication process of PRRSV [17]. Recent studies have found that germacrone has a significant anti-cancer effect, can inhibit the progress of colorectal cancer, liver cancer, breast cancer, lung cancer and other cancers, and has the characteristics of high efficiency and low toxicity [18][19][20]. Lim et al found that germacrone inhibited breast cancer progression by inhibiting estrogen receptor α and synergizing with other antitumor drugs 5-fluorouracil and methotrexate [21].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the anticancer activity of Saussurea costus is mainly due to its major components sesquiterpenoids [36,37]. Germacrone is a sesquiterpene and has certain anticancer effects on glioma, retinoblastoma, breast cancer, liver cancer, prostate cancer, and colon cancer [12][13][14][15][16][17]38]. However, the pharmacological effects and mechanisms of germacrone against human ESCC are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%